ANALISIS KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA 2018-2021 - Herdiansyah Herdiansyah; Rachmatullaily Rachmatullaily (JURNAL PUNDI, 2023)
This type of research is descriptive and verification using secondary data, while the sampling method uses purposive sampling in order to obtain 7 companies from 12 Pharmaceutical Sub-Sector companies listed on the Indonesia Stock Exchange. The data analysis methods in this study are descriptive statistics, multiple linear regression analysis and hypothesis testing using SPSS 26 software. The results show that the development of CR, DER, EPS and ROA in Sub-Pharmaceutical companies has increased and decreased as well as the development of stock returns in the Pharmaceutical Sub-Sector from 2018-2021 fluctuated every year. (1) Partially DER has an effect on stock returns. Meanwhile, CR, EPS and ROA have no effect on stock returns. Then simultaneously that H5 is rejected which means that there is no effect of Current Ratio, Debt to Equity Ratio, Earning Per Share and Return On Assets on stock returns.Keywords: : Current Asset, Debt to Equity Ratio, Earning Per Share, Return On Asset, Stock Return